Pharmacist-Developed Sedation Protocol and Impact on Ventilator Days. (August 2013) - Hahn, Lindsay; Beall, Jennifer; Turner, R. Scott; Woolley, Thomas W.; Hahn, Martin
Background: Up to one-third of intensive care unit (ICU) patients require mechanical ventilation. Mechanical ventilation is associated with numerous complications including ventilator-induced lung injury and gastrointestinal bleeding due to ulcerations. 1 Sedation protocols are used in order to optimize treatment and decrease days spent on mechanical ventilation. Objective: The purpose of this trial is to evaluate the effectiveness of an ICU sedation protocol. The primary end point was days on mechanical ventilation. Design: A retrospective chart review was performed. The medical records of 21 patients treated prior to the protocol and 21 patients treated after protocol implementation were reviewed. Results: The duration of mechanical ventilation was decreased in the postprotocol patients compared to the preprotocol patients. The mean duration of mechanical ventilation in the preprotocol group was 6.39 ± 5.24 versus the postprotocol group which was 3.78 ± 3.21 days. After implementing the sedation protocol, the number of days to extubation was decreased by 2.61 days. Conclusion: The use of sedation protocols can decrease the days spent on mechanical ventilation. The results also illustrate the enormous impact pharmacists have on policy and protocol development.